A proposed experimental test of proton-driven plasma wakefield acceleration based on CERN SPS - Xia, G. (2011)
Proton-bunch driven plasma wakefield acceleration (PDPWA) has been proposed as an approach to accelerate electron beam to TeV energy regime in a single plasma section. An experimental test has recently proposed to demonstrate the capability of PDPWA by using proton beams from the CERN SPS. The layout of the experiment is introduced. Particle-in-cell simulation results based on the realistic beam parameters are presented.